Repeated CT scans in trauma transfers: An analysis of indications, radiation dose exposure, and costs. Issue 88 (March 2017) - Hinzpeter, Ricarda; Sprengel, Kai; Wanner, Guido A.; Mildenberger, Peter; Alkadhi, Hatem
Highlights: Repetition of CT in trauma patients occurs relatively often. Repetition of CT is mainly caused by inadequate image data transfer. Potentially preventable CT examinations add radiation dose to patients. Repeated CT is associated with excess costs to the health care system. Abstract: Objectives: To identify the number of CT scans repeated in acute trauma patients receiving imaging before being referred to a trauma center, to define indications, and to assess radiation doses and costs of repeated CT. Methods: This retrospective study included all adult trauma patients transferred from other hospitals to a Level-I trauma center during 2014. Indications for repeated CT scans were categorized into: inadequate CT image data transfer, poor image quality, repetition of head CT after head injury together with completion to whole-body CT (WBCT), and follow-up of injury known from previous CT. Radiation doses from repeated CT were determined; costs were calculated using a nation-wide fee schedule. Results: Within one year, 85/298 (28.5%) trauma patients were transferred from another hospital because of severe head injury (n = 45, 53%) and major body trauma (n = 23;27%) not manageable in the referring hospital, repatriation from a foreign country (n = 14;16.5%), and no ICU-capacity (n = 3;3.5%). Of these 85 patients, 74 (87%) had repeated CT in our center because of inadequate CT data transfer (n = 29;39%), repetition of head CT with completion to WBCT (n = 24;32.5%), and follow-up of known injury (n = 21;28.5%). None occurred because of poor image quality. Cumulative dose length product (DLP) and annual costs of potential preventable, repeated CT (inadequate data transfer) was 631mSv (81′304mGy*cm) and 35′233€, respectively. Conclusion: A considerable number of transferred trauma patients undergo potentially preventable, repeated CT, adding radiation dose to patients and costs to the health care system.